Potential of Onion Skin, Luffa cylindrica, and Corn Cob as Cellulose Sources: A Study of Their Proximate, Ultimate, and Morphological Properties - Hyelni G. MSHELIA; Abdulfatai JIMOH; Mohammed A. EVUTI; Abubakar A. IBRAHIM; Abdulwahab GIWA; Adeola G. OLUGBENGA (FUDMA Journal of Engineering and Technology, 2025)
Nigeria grows a lot of onions and Corn, which are popular foods widely eaten within the population. Luffa cylindrica also grows widely in most areas of the country as a wild plant or weed due to the warm climate, which favors its growth. The onion skin, Luffa cylindrica, and corn cobs are agro-wastes that pose disposal challenges but offer potential as renewable sources of cellulose for industrial applications. These biomasses were processed into powdered form and subjected to characterization for evaluation of their suitability for cellulose extraction. The biomass was dried, ground, and sieved to uniform particle sizes. Proximate, ultimate, and chemical composition analyses were conducted, alongside Scanning Electron Microscopy coupled with Energy Dispersive X-Ray Spectroscopy (SEM/EDX). Differential Thermal/Gravimetric Analysis (DTA/TGA) was also carried out on these samples. The proximate analysis revealed high carbohydrate contents (86.065%, 83.868%, and 76.997%) for onion skin, Luffa, and corn cobs, respectively, reflecting a higher proportion of cellulose, a polysaccharide found in higher proportions in plant biomass. EDX analysis confirmed the presence of high carbon at 47.06%, 56.9%, and 55.05%, as reflected in the ultimate analysis at 48.38%, 59.33%, and 57.92%, respectively. Meanwhile, SEM images revealed rough, well-defined surface morphologies favorable for chemical interaction. TGA results showed significant thermal degradation from 200–400 °C, correlating with cellulose decomposition. Chemical composition analysis showed cellulose contents of 59.05±0.1%, 58.82±0.1%, and 55.86±0.2% for onion, luffa, and corncob, respectively. These findings give confirmation that these biomasses possess high cellulose content and suitable structural characteristics that make them good choices for cellulose extraction. The cellulose can be used in environmentally friendly technologies, such as industrial wastewater treatment.